Melatonin Alleviates Cardiac Function in Sepsis-Caused Myocarditis via Maintenance of Mitochondrial Function - Chen, Liyang; Tian, Qing; Shi, Zhiguang; Qiu, Yu; Lu, Qiulun; Liu, Chao (Frontiers in Nutrition, 2021)
Melatonin (N-acetyl-5-methoxytryptamine) has been shown to have a cardioprotective effect against myocarditis. However, the mechanisms underlying the protective role of melatonin in sepsis-induced myocarditis remain to be revealed. In this study, melatonin was administrated to mice 14 days before cecal ligation puncture surgery. Echocardiography results showed that melatonin alleviated cardiac dysfunction in sepsis-induced myocarditis. Melatonin reduced cardiac inflammation by inhibiting the expression of Il-1α, Il-1β, Il-6, and Mcp-1 mRNA levels. RNA sequencing assays with heart tissues showed melatonin maintains the mitochondrial function in sepsis-caused myocarditis. Additionally, the production of ROS in heart tissues was suppressed by melatonin. Taken together, in evaluating the therapeutic effect of MLT on sepsis-induced myocarditis, the results showed that MLT alleviated cardiac damage by regulating the mitochondrial function and mitochondrial ROS.